Electrocatalytically modified microelectrodes for the detection of hydrogen peroxide at blood cells from swine with induced trauma. (1st September 2020) - Hellmann, A.; Daboss, S.; Zink, F.; Hartmann, C.; Radermacher, P.; Kranz, C.
Abstract: Reactive oxygen species (ROS) play a crucial role in both physiological and pathological process such as intracellular signaling and host defense. However, elevated ROS levels lead to protein oxidation, lipid peroxidation, and DNA damage. Inflammation and tissue injury are associated with increased ROS production. The role of hydrogen peroxide (H2 O2 ), which is an important representative of ROS within these physiological processes, is still not fully understood. Here, we present microelectrodes modified with electrocatalytically active platinum-black (Pt-black) or Prussian blue (PB) films for the detection of extracellular H2 O2 . Detection limits in the nanomolar range with limits of detection (LOD) of 201 ± 10 nM for PB and of 214 ± 2 nM for Pt-black, respectively, could be achieved, thereby enabling the detection/quantification of extracellular H2 O2 levels at porcine peripheral blood mononuclear cells (PBMCs) and at granulocytes from swine undergoing hemorrhagic shock and resuscitation or undergoing hemorrhagic shock subsequent to an acute subdural hematoma and resuscitation. Increased levels of H2 O2 could be observed due to increased oxidative stress, especially during the acute trauma phase. The simultaneous detection of catecholamines such as norepinephrine administered during the recovery phase using a dual microelectrode assembly and carbon fiber electrodes was also investigated.